Palhada de cana-de-açúcar como substrato alternativo para plantas ornamentais - Coimbra, Antônio Mesaque Bandeira (Universidade Federal de São Carlos, 2025)
Brazilian floriculture has experienced significant growth in both production and economic value, with the state of São Paulo being one of the main contributors to this progress. One of the key inputs in ornamental plant cultivation is the substrate, with coconut fiber and pine bark being the most commonly used bases. Despite the many advantages these substrates offer, their use also faces challenges, such as the distance between the production site and the ornamental cultivation area, the presence of phytotoxic substances, the need for processing, and, more recently, the shift of coconut production to the Amazon rainforest, directly contributing to deforestation. In recent years, the sugarcane industry has undergone a transition from using burnt cane to raw cane, resulting in a large amount of straw residue left in the field. Currently, this straw is removed and used as an energy source or for the production of second-generation ethanol. With a total area of 8.3 million hectares—half of which is located in São Paulo—sugarcane production can generate between 10 to 30 tons per hectare of straw, depending on the variety and age of the plantation. In this context, the aim of this study was to evaluate the potential use of sugarcane straw as a substrate for the cultivation of orchids and begonias. The experiment used a Phalaenopsis progeny with seedlings approximately 10–15 cm in diameter, and Begonia maculata clones obtained through cuttings. A completely randomized design in a 2x5 factorial scheme was used, with one factor being the substrate—comprising mixtures of sugarcane straw and commercial substrate in proportions ranging from 0 to 100% straw—and the second factor being the fertilizer dose, using 75% and 100% of the recommended fertilization rate. Additionally, analyses were performed to better understand the physical and chemical characteristics of the substrates, including chemical composition, total water retention, water loss over time under greenhouse conditions, and straw decomposition rate. For begonia cultivation, the substrate with 25% sugarcane straw (C25) showed the best performance, promoting greater vegetative growth, chlorophyll synthesis, and biomass accumulation, while the 100% straw substrate (C100) showed limitations due to lower nutrient availability. For Phalaenopsis orchid cultivation, substrates with up to 50% straw (C50) yielded better growth and flowering results, whereas the full straw substrate (C100) negatively affected aesthetic features such as petal size. Sugarcane straw showed a faster decomposition rate, retaining only 44% of its mass after 220 days, while the commercial substrate decomposed more slowly, favoring long-term nutrient supply. In terms of water retention, straw stood out for its higher retention (553% w/w), but also had a higher rate of water loss, requiring more frequent irrigation. The commercial begonia substrate had moderate retention, while the orchid substrate had the lowest capacity. In the chemical analysis, the Carolina Soil® substrate showed a more balanced nutrient composition, while sugarcane straw presented lower concentrations of soluble nutrients. The results demonstrate the potential of sugarcane straw as an alternative substrate when mixed up to 50% by volume with commercial substrates, making its use viable for cultivating begonias and Phalaenopsis orchids.
Sugarcane straw as an alternative substrate for ornamental plants
Keywords: Plantas ornamentais; Substratos; Palhada; Cana-de-açúcar; Casca de pinus; Fibra de coco; Ornamentals; Substrates; Straw; Sugarcane; Pine bark; Coconut fiber; CIENCIAS AGRARIAS::AGRONOMIA::FLORICULTURA, PARQUES E JARDINS; CIENCIAS BIOLOGICAS::BOTANICA::FISIOLOGIA VEGETAL::NUTRICAO E CRESCIMENTO VEGETAL